Analisis praktik jual beli saat azan Jumat (studi komparatif pemikiran Imam Syafi’i dan Imam Malik) - Elizatun, Elizatun (Prodi Perbandingan Madzab Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2025)
This research discusses the practice of buying and selling that occurs during the second call to prayer, a moment that in Islamic law has special provisions. This prohibition refers to QS. Al-Jumu'ah verse 9, which instructs Muslims to abandon buying and selling and immediately perform the Friday prayer. This study aims to analyze the views of Imam Shafi'i and Imam Malik regarding the law of buying and selling during the Friday call to prayer, and to identify the similarities and differences between them. The method used is literature research with a descriptive-comparative approach, analyzed deductively and inductively. The results show that according to Imam Syafi'i, the practice is haram for those who are obliged to pray on Friday, but the contract is still valid. While Imam Malik stated that in addition to being haram, the sale contract is also void. Both of them agree that the prohibition starts from the second adhan, covers all forms of transactions that distract from prayer, and is sinful if done by those who are obliged. However, they differ on the validity of the contract and the ruling on the one who is not obliged to do it. This comparison shows the methodological differences in ruling between the two imams.